Modeling Consumer Intention to Use Electric Vehicles in Indonesia: Extending UTAUT2 with Risk, Trust, and Digital Literacy - Prasetyo Harisandi; Syahrul Alim; Purwanto Purwanto; Hilma Kusumawati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
The transition toward sustainable mobility has positioned electric vehicles (EVs) as a strategic solution to reduce carbon emissions and dependence on fossil fuels. However, the adoption rate of EVs in Indonesia remains relatively low, indicating the need to better understand the factors influencing consumer adoption intentions. This study aims to examine consumers’ behavioral intention to adopt electric vehicles in Indonesia by extending the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) with perceived risk, trust, and digital literacy. A quantitative research design was employed using a cross-sectional survey of 185 respondents who are familiar with electric vehicle technology. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that UTAUT2 has a significant positive effect on consumers’ behavioral intention to adopt electric vehicles. Furthermore, perceived risk was found to negatively mediate the relationship between UTAUT2 and behavioral intention, while trust and digital literacy positively mediate this relationship. These findings suggest that although technological benefits encourage EV adoption, psychological barriers and digital readiness play a crucial role in shaping consumer intentions. This study contributes to the technology adoption and sustainable mobility literature by providing an extended UTAUT2 model tailored to the Indonesian context. Practically, the findings offer insights for policymakers and industry stakeholders to develop strategies that reduce perceived risk, enhance trust, and improve digital literacy to accelerate electric vehicle adoption in Indonesia.